Neuroprotective Effects of Tetramethylpyrazine against Dopaminergic Neuron Injury in a Rat Model of Parkinson's Disease Induced by MPTP - Lu, Chen (Ivyspring International Publisher, 2014)
Parkinson's disease (PD) is the second most prevalent progressive neurodegenerative disease. Although several hypotheses have been proposed to explain the pathogenesis of PD, apoptotic cell death and oxidative stress are the most prevalent mechanisms. Tetramethylpyrazine (TMP) is a biological component that has been extracted from Ligusticum wallichii Franchat (ChuanXiong), which exhibits anti-apoptotic and antioxidant roles. In the current study, we aimed to investigate the possible protective effect of TMP against dopaminergic neuron injury in a rat model of Parkinson's disease induced by MPTP and to elucidate probable molecular mechanisms. The results showed that TMP could notably prevent MPTP-induced dopaminergic neurons damage, reflected by improvement of motor deficits, enhancement of TH expression and the content of dopamine and its metabolite, DOPAC. We observed MPTP-induced activation of mitochondrial apoptotic death pathway, evidenced by up-regulation of Bax, down-regulation of Bcl-2, release of cytochrome c and cleavage of caspase 3, which was significantly inhibited by TMP. Moreover, TMP could prevent MPTP-increased TBARS level and MPTP-decreased GSH level, indicating the antioxidant role of TMP in PD model. And the antioxidant role of TMP attributes to the prevention of MPTP-induced reduction of Nrf2 and GCLc expression. In conclusion, in MPTP-induced PD model, TMP prevents the down-regulation of Nrf2 and GCLc, maintaining redox balance and inhibiting apoptosis, leading to the attenuation of dopaminergic neuron damage. The effectiveness of TMP in treating PD potentially leads to interesting therapeutic perspectives.